Do Financial Advisors have Consumers' Best Interests? Not Always, but Trust is Key, say Experts - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
In a world of volatile markets and complex financial products, getting financial advice from professional financial planners and advisers might seem like a good idea for those for those trying to meet their financial goals. However, finding good, impartial and suitable advice might be akin to finding a needle in the proverbial haystack.